PRE-HARVEST BIOMARKERS FOR IMPROVED STORABILITY AND PROCESSING QUALITY OF POTATOES UNDER HEAP STORAGE - Mehta, Ashiv (Potato Journal, 2016)
An improved heap storage technology with the use of CIPC (isopropyl N-(3-chlorophenyl) carbamate) has been developed for short-term storage of potatoes. Effect of tuber maturity and curing of skin on storage losses and processing quality was studied in three potato cultivars harvested at two maturity dates direct/after a curing period of 15 days following dehaulming of the crop to standardize pre-harvest factors to minimize losses. Potatoes from different treatments were stored with/without CIPC treatment @ 20 mg a.i./kg of tubers. Curing of potatoes reduced losses (physiological + rotting) in potatoes compared to direct harvest at both maturity levels. CIPC treatment significantly reduced losses in potatoes compared to control (untreated) particularly in cured potatoes up to 105 days of storage Processing quality was improved by maturity while curing of potatoes did not record much effect. Reducing sugar (RS) content was significantly higher in immature tubers of Kufri Jyoti and Kufri Pukhraj. While in Kufri Chipsona-1, RS content remained low (<150 mg/100 g fresh weight) at harvest and during storage in heaps and chip colour was acceptable in all treatments in CIPC treated and untreated potatoes up to 105 days of storage. Potatoes of Kufri Chipsona-1 harvested at different maturity levels in North-western plains can thus, meet the short-term needs of the processing industry during February-June.